Gendered political empowerment in Iraq: examining women's engagement in the post-2003 political landscape - Hussein, Jamal Mohammed Ameen; Jalal Nori, Abdulwahed (IIUM Press, 2024)
The present article examines women's political engagement in Iraq following 2003, presenting an evaluation of their current political milieu. The text provides insight into the rise of multiple women's groups, clarifying their goals and actions. The article delves into the unique difficulties and hindrances faced by proponents of women's rights in presentday Iraq. In the aftermath of the collapse of the Ba'athist government, a promising window of opportunity emerged for women to participate in the political sphere. As a result, female citizens of Iraq have attained a noteworthy degree of political engagement, obtaining roles within the governmental and parliamentary spheres. Despite persistent efforts, individuals in Iraq are still facing a range of obstacles stemming from tribal, sectarian, customary, and legal factors, which are primarily influenced by prevailing patriarchal and sectarian ideologies. This research employs historical, descriptive, and political analysis to showcase the active participation of Iraqi women in the political and social landscape of Iraq. This statement highlights their continuous involvement in promoting the progress of the political system, as evidenced by their occupancy of various political positions.